Pérou 2001 : vers une démocratie sans adjectifs ? - Laurence Crot (Cahiers des Amériques Latines)
The author seeks to provide an account of the main characteristics of the process of democratic disintegration which took place in Peru throughout the last decade. Since Alberto Fujimori took office in 1990, the Peruvian society, while hoping for a more egalitarian repartition of political power, has been relentlessly deprived of the mechanisms of popular governance which constitute the very foundations of a democratic society and its political participation: deliberation, representation, and the guarantee of constitutional freedoms. The democratic transition and the 2001 elections carry with them the hope that the new government will be willing and able to endow Peru with the necessary institutions to ensure the true rule of law.